Sex-specific effect of APOAV variant (Val153>Met) on plasma levels of high-density lipoprotein cholesterol - Hubacek, Jaroslav A; Skodová, Zdena; Adámková, Vera; Lánská, Vera; Poledne, Rudolf (Metabolism: clinical and experimental, 2005)
The importance of the APOAV gene for the determination of plasma triglyceride levels has been suggested by creations of transgenic and knockout mice and confirmed in population studies. We examined whether the newly detected APOAV variant is associated with plasma lipid levels and risk of myocardial infarction (MI). APOAV polymorphism (Val153>Met) was genotyped in 1191 males and 1368 females representatively selected from the Czech population. Lipid levels were analyzed in 1997 and 2001 in all individuals. Subsequently, we have analyzed the genotype frequencies of APOAV polymorphism in 435 male patients with MI. Val153>Met variation in the APOAV gene affects the plasma high-density lipoprotein cholesterol levels showing a higher level in Val/Val homozygotes than in Met carriers in both years (1.51 +/- 0.36 and 1.52 +/- 0.37 mmol/L compared with 1.42 +/- 0.33 and 1.39 +/- 0.35 mmol/L, P < .01). This association has been observed in females but not in males. Other analyzed lipid parameters (total cholesterol, low-density lipoprotein cholesterol, and triglycerides) have not been associated with APOAV Val153>Met variant. In a group of patients with MI, the frequency of the Met153 carriers was not significantly different from the male population sample (6.5% vs 6.4%). Val153>Met variation in the APOAV gene plays a sex-specific role in genetic determination of plasma high-density lipoprotein cholesterol levels, but does not influence risk of MI in males.
Keywords: Gene Frequency; Male; HDL-cholesterol; apolipoproteiny; Apolipoproteins; Genotype; polymorfismus genetický; Cholesterol, HDL; sexuální faktory; Adult; Aged; dospělí; mužské pohlaví; senioři; triglyceridy; Polymorphism, Genetic; infarkt myokardu; frekvence genu; lidé; apolipoproteiny A; ženské pohlaví; Humans; Sex Factors; Myocardial Infarction; apolipoprotein A-V; genotyp; Triglycerides; Apolipoprotein A-V; Female; lidé středního věku; Apolipoproteins A; Middle Aged